2019
DOI: 10.1111/jop.12816
|View full text |Cite
|
Sign up to set email alerts
|

Risk of high‐grade malignancy in parotid gland tumors as classified by the Milan System for Reporting Salivary Gland Cytopathology

Abstract: Background The Milan System for Reporting Salivary Gland Cytopathology (Milan System) has previously shown its diagnostic utility by categorizing the seven cytology findings in salivary gland lesions. However, there has been lack of study about the risk of high‐grade malignancy in the cytology diagnosis based on the Milan System. Thus, we tried to identify the diagnostic ability of the Milan System for high‐grade malignancy and to suggest an improved diagnostic approach for preoperative estimation of high‐grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 32 publications
2
31
4
Order By: Relevance
“…A distinct advantage of MSRSGC was that it maximizes clinical discretion and when coupled with appropriate clinical and imaging findings results in optimal follow‐up for the majority of patients . Park et al reported that combining the Milan system category (malignant) with the presence of nodal metastasis is suggestive of high‐grade malignancy with an acceptable diagnostic sensitivity (0.889‐0.963) and negative predictive value (0.900‐0.966) …”
Section: Discussionsupporting
confidence: 87%
“…A distinct advantage of MSRSGC was that it maximizes clinical discretion and when coupled with appropriate clinical and imaging findings results in optimal follow‐up for the majority of patients . Park et al reported that combining the Milan system category (malignant) with the presence of nodal metastasis is suggestive of high‐grade malignancy with an acceptable diagnostic sensitivity (0.889‐0.963) and negative predictive value (0.900‐0.966) …”
Section: Discussionsupporting
confidence: 87%
“…A high proportion (25.6%) of cases were considered ND. This is somewhat higher than that reported in other studies by [4,[7][8][9][10][11]. This may be related to the method of sample collection.…”
Section: Discussioncontrasting
confidence: 62%
“…Using ICC and/or FISH analysis, the ROM for the M category was determined to be 100%. Park et al, observed a similar risk for this category, in accordance with the MSRSGC [4].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A recent study estimated the risk of high‐grade malignancy to be 16.7% for SFM and 55.9% for the malignant category of MSRSGC, but it did not comment on the accuracy of predicting a low grade versus a high grade with a cytologic specimen . Our study, though admittedly limited by its small sample size, showed high accuracy in favoring a high‐grade malignancy on FNA because all 5 cases deemed high‐grade on cytology showed high‐grade carcinoma on resection.…”
Section: Discussioncontrasting
confidence: 55%